Penggunaan Model Hec-Hms Dalam Pemenuhan Air Baku Di Kabupaten Dan Kota Jayapura (Annual Water Allocation Plan For Sentani Lake Watershed) - Wambrauw, Neilzen Wiliam; Widyastuti, Ira; Rante, Harmonis; Mujiati, Mujiati; Julison, Bernathius (Syntax Literate, 2025)
The location of the study in this study is the Sentani watershed which is located in Jayapura City and Jayapura Regency. In the Sentani watershed, there is Lake Sentani which has potential utilization in the form of a Drinking Water Supply System (SPAM), Irrigation Needs of Agricultural Areas, Power Plants, Utilization of Business Development in the Fisheries Sector and Lake Ecotourism Destination Areas. With the growing utilization in the Sentani watershed, an analysis of water allocation is needed to determine the ability of the Sentani watershed to meet its needs. The Head of PDAM Jayapura explained that Lake Sentani has the potential to be an alternative to overcome the reduced water discharge and water supply for the community in Jayapura Regency. So it is hoped that this research can contribute to providing a foothold for water utilization recommendations for the community in Jayapura Regency. The results of this study show that Lake Sentani can meet water needs both with existing intakes and with the fulfillment of new needs to be developed. The total raw water taken based on the existing intake is 0.926 m^3/s and the plan to increase the raw water intake in Jayapura district is 0.125 m^3/s.